Tinjauan Hasil Pemeriksaan NS1 Dan IgG/IgM Dengue Metode Imunokromatografi Terhadap Hasil Pemeriksaan Total Jumlah Dan Indeks Trombosit Pada Penderita Demam Dengue - Yaumil Fachni Tandjungbulu; Alfin Resya Virgiawan; Widarti Widarti; Farhah Ramadhani Suparmin (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Dengue fever carries a risk of developing dengue shock syndrome, which can be fatal if not diagnosed and treated promptly. In addition to taking a medical history and performing a physical examination, laboratory tests are required. Laboratory tests that can be conducted include dengue NS1 testing, dengue IgG and IgM testing, and platelet count and platelet index measurements. This study aims to determine the correlation between NS1 and dengue IgG IgM test results and total platelet count and platelet indices (MPV, PDW, P-LCR, and PCT) in patients with dengue fever. This study is a correlational study using a cross-sectional analytical approach, employing purposive sampling techniques, and obtained 40 samples that met the study criteria. The study was conducted at the Clinical Pathology Laboratory of Hasanuddin University Hospital in Makassar from December 1, 2024, to February 28, 2025. The results of the study showed that there was a significant correlation between dengue IgG test results and total platelet count (p=0.032, p<0.05) and PDW (p=0.031, p<0.05), while there was no significant correlation with PCT test results (p=0.788, p>0.05). For dengue IgM and NS1 dengue test results, no significant correlation was found with total platelet count (p=0.565, p=0.624, p>0.05), PDW (p=0.728, p=0.188, p>0.05), and PCT (p=0.841, p=0.454 (p > 0.05). The results of MPV and P-LCR tests showed consistent results, so no statistical analysis was performed. It was concluded that total platelet count and platelet index PDW could serve as potential laboratory biomarkers for screening, diagnosis, and monitoring of dengue-infected patients based on dengue IgG test results. Keywords: Dengue Fever; Dengue IgG IgM; Platelet Index; Platelet Count; Dengue NS1